Analisis Digital Marketing Menggunakan Metode Mix 4C Pada UMKM Kasab Aceh Di Wilayah Gampong Parom Kabupaten Nagan Raya - Adria Adria; Banta Diman; Ida Fujari (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This research analyzes the implementation of digital marketing strategies using the 4C mix method (Customer, Cost, Convenience, Communication) at Aceh Kasab UMKM in Gampong Parom, Nagan Raya Regency. The study was prompted by a shift from the traditional 4P marketing method (Product, Price, Place, Promotion) to a more adaptive digital approach in the technological era. A qualitative approach was employed, and data were collected through triangulation of information sources. The findings indicate that while opportunities for digital marketing are promising, challenges remain, particularly regarding limited human resources skilled in technology and a lack of understanding of digital marketing. Additionally, the limited availability of delivery services in the area poses obstacles to goods distribution. However, the increasing presence of celebrities and influencers in Nagan Raya Regency presents opportunities to effectively market Acehnese products. The analysis suggests that Kasab Aceh UMKM products will continue to attract consumers, especially due to the local community's commitment to preserving traditions and culture. Stable production costs further strengthen the position of Kasab Aceh UMKM. To optimize digital marketing strategies, it is essential to address issues related to delivery convenience and communication with consumers.